Pengaruh Fasilitas Kerja, Motivasi Kerja, Dan Disiplin Kerja Terhadap Kinerja Pegawai Pemerintahan (Studi Kasus Kantor Kecamatan Lowokwaru Kota Malang) - Mochammad Bachtiar Affandie; Muhammad Mansur; Afi Rahmat Slamet (UNIVERSITAS ISLAM MALANG, 2020)
AbstractThis study aims to determine the effect of work facilities, work motivation, and work discipline simultaneously on employee performance. Sources of data used in the study are using primary data and data collection methods using questionnaires distributed to respondents. The population used in this study were employees of the Lowokwaru District Office of Malang City with a total of 40 employees. The results obtained by using multiple linear regression test Y = 2.508 + 0.289 + 0.293 + 0.290 + e, and the hypothesis test of this study uses the coefficient of determination test, F test, and t test. The results of this study indicate that work facilities partially affect employee performance, work motivation affects employee performance, work discipline affects employee performance. While simultaneous work facilities, work motivation, and work discipline affect employee performance. Keywords: Work Facilities, Work Motivation, Work Discipline And Employee Performance